Identification of novel source of resistance to powdery mildew in bottle gourd (Lagenaria siceraria) - SINGH, JOGENDRA; RANJAN, J K; TOMAR, B S; SINGH, A K; JAT, G S; MISHRA, G P; AKHTAR, JAMEEL; PRAGYA; RAJKIRAN; VERMA, M (The Indian Journal of Agricultural Sciences, 2025)
Powdery mildew caused by Podosphaera xanthii is one of the prevalent fungal diseases causing significant economic loss in bottle gourd [Lagenaria siceraria (Mol.) Standl.]. The present study was carried out during 2021 to 2023 at ICAR-Indian Agricultural Research Institute, New Delhi to identify the novel source of resistance to powdery mildew in bottle gourd. About 82 diverse genotypes of bottle gourd were screened under controlled conditions and experiment was conducted in three replications with five seedlings in each germplasm. The seedlings were artificially inoculated with powdery mildew spores using dusting method at cotyledonary leaf stage. Disease severity on 0–9 scale was recorded from 7–28 days post inoculation. The mean per cent disease index (PDI) value at 4 weeks post inoculation (WPI) ranged from 0.00–98.52% (2021), 0.74–93.33% (2022), and 0.00–97.04% (2023) across the years of screening. Disease pressure was high over the years as indicated by higher PDI shown by susceptible genotypes. A rapid increase in PDI was recorded during 1–2 WPI, reaching highest at 4 WPI. This suggests that preventive measures to control powdery mildew should be implemented as soon as symptoms appear in the field. Three genotypes, viz. EC800996, EC800998 and IC337078 were identified as resistant having low pooled mean PDI value ranging from 0.00–8.89%. Moderate resistant reaction was reported in Pusa Santusthi, IC296733, EC1085257, EC1085231, IC567545, and IC567534. Additionally, low values of AUDPC and rAUDPC further indicates slow progression of disease after inoculation in resistant and moderately resistant genotypes. The resistant genotypes identified may serve as potential source for resistance breeding against powdery mildew in bottle gourd.